The relationship between self-efficacy and level of critical thinking of high school students in Selangor, Malaysia - Mohd Ali, Ju Aini; Mohd Shahabuddin, Khairul Najlah; Ahmad Nasir, Nurathirah; M. Munisamy, Thamarai; Zhang, Yue; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
In this day and age, critical thinking is one of the most important aspects of education as educators need to pay more attention on producing students with higher order level of thinking. Critical thinking skills have been introduced in the curriculum to help develop strategic thinking skills in students. This study is aimed to investigate the relationship between student’s self-efficacy and critical thinking in student at High School in Selangor. A simple random sampling of 100 students were tested by using Sherer et al.’s (1982) General Self-efficacy Scale and The Cornell Critical Thinking test. The expected result of this study is it will show that there is a positive relationship between critical thinking and self-efficacy belief. Self-efficacy belief will play a role in students’ critical thinking.